2004
DOI: 10.2193/0091-7648(2004)32[427:dochft]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of critical habitat for the endangered Nelson's bighorn sheep in southern California

Abstract: The United States Fish and Wildlife Service's (USFWS) designation of critical habitat for the endangered Nelson's bighorn sheep (Ovis canadensis nelsoni) in the Peninsular Ranges of southern California has been controversial because of an absence of a quantitative, repeatable scientific approach to the designation of critical habitat. We used 12,411 locations of Nelson's bighorn sheep collected from 1984–1998 to evaluate habitat use within 398 km2 of the USFWS‐designated critical habitat in the northern Santa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 27 publications
1
79
0
5
Order By: Relevance
“…Virtually every habitat model developed for desert bighorn sheep has identified water as an important correlate of sheep use (McCarty and Bailey, 1994;Bleich et al, 1997;Andrews et al, 1999;Turner et al, 2004;Oehler et al, 2005;Sappington et al, 2007). Further, an analysis of 20th Century extinction patterns of desert bighorn sheep populations in California found the existence of predictable surface water, in addition to elevation and maximum precipitation, to be strongly correlated with population persistence (Epps et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtually every habitat model developed for desert bighorn sheep has identified water as an important correlate of sheep use (McCarty and Bailey, 1994;Bleich et al, 1997;Andrews et al, 1999;Turner et al, 2004;Oehler et al, 2005;Sappington et al, 2007). Further, an analysis of 20th Century extinction patterns of desert bighorn sheep populations in California found the existence of predictable surface water, in addition to elevation and maximum precipitation, to be strongly correlated with population persistence (Epps et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…During summer months, water sources are considered as an essential component of suitable habitat for nearly all desert bighorn sheep populations (Bleich et al, 1997;Andrews et al, 1999;Turner et al, 2004;Oehler et al, 2005;Sappington et al, 2007;but, see Warrick and Krausman, 1989) and the presence of dependable water sources has been strongly correlated with population persistence (Epps et al, 2004). Artificial water sources have been used for decades to enhance and restore habitat for desert bighorn sheep (Halloran and Deming, 1958;Weaver et al, 1958;Werner, 1984), but the benefits are not always obvious.…”
Section: Introductionmentioning
confidence: 99%
“…Despite strong evidence that water plays an important role in the life histories of arid-land ungulates and its profound influence on habitat selection by mountain sheep (Andrew et al, 1999;Bleich et al, 1997;Oehler et al, 2005;Rubin et al, 2009;Turner et al, 2004), particularly during summer (Bristow, 1998;Waddell et al, 2007), provision of water sources as a conservation strategy remains controversial (Bleich, 2005;Krausman et al, 2006). Even ''long term'' manipulative experiments have not provided unequivocal results that will assist land managers in making informed decisions about the contributions of wildlife water developments to conservation programs.…”
Section: Discussionmentioning
confidence: 99%
“…For mountain sheep (Ovis canadensis) and mule deer (Odocoileus hemionus), proximity to surface water during summer (Andrew et al, 1999;Bleich et al, 1997;Blong and Pollard, 1968;Oehler et al, 2005;Ordway and Krausman, 1986;Turner et al, 2004), visitation rates (Blong and Pollard, 1968;Hervert and Krausman, 1986;Marshal et al, 2006a;Turner, 1973), seasonality of use (Bleich et al, 1997;Bristow, 1998;Waddell et al, 2007), and water consumption rates (Hazam and Krausman, 1988;Turner, 1970Turner, , 1973 all demonstrate the importance of surface water to those ungulates. Moreover, Turner (1973) demonstrated that water content of mountain sheep diets during summer is insufficient for meeting evaporative water losses; as a result, those ruminants must rely on sources of free water to maintain water balance.…”
Section: Introductionmentioning
confidence: 99%
“…In the BMEMP, service area around a water development was considered to be 1.5 miles for general wildlife use. Turner et al (2004) found that 97% of desert bighorn collar locations were within 1.86 miles of water. Some consider the highest ranking habitat to be within two miles of a permanent water source (Cunningham 1989, Hansen 1980); yet Wilson (1975) found desert bighorn up to three miles from water.…”
Section: Watermentioning
confidence: 99%